Description of a new species of the rare genus Epacrolaimus Andrássy, 2000 (Dorylaimida, Aporcelaimidae) and new data on male of Paraxonchium laetificans (Andrássy, 1956) Altherr & Loof, 1969 (Dorylaimida, Paraxonchiidae) from Iran - Pedram, Majid; Pourjam, Ebrahim; Vinciguerra2, Maria T. (Zootaxa, 2012)
Epacrolaimus reyesi n. sp., an amphimictic species of a rare nematode genus, is described and illustrated. The new species ischaracterised by its long body (7.23–7.87 mm), 32 µm wide lip region, with well developed and distinct lips and liplets pro-vided with longitudinal corrugation on their inner surface; 19–22 µm long odontostyle with a wide, arched aperture occupyingca 85% of its length; 45–56 µm long odontophore; 55–67 µm long rounded tail, nine regularly spaced ventromedian supple-ments in males and 135–145 µm long spicules. The new species is compared with two other known species of the genus,namely E. declinatoaculeatus (Kreis, 1924) Andrássy, 2000 and E. imperator Andrássy, 2000. Compared to the former, thenew species has a rounded tail in females vs bluntly conoid, rounded on tip or with a minute peg, shorter tail (55–67 vs 63–75µm) shorter spicules (135–145 vs 215 µm) and fewer male copulatory supplements (9 vs 12). Compared to the latter species, E.reyesi n. sp. is wider at the midbody region (172–178 vs 156–160 µm), and has a shorter tail (55–67 vs 84 µm in females and58–65 vs 70–86 µm in males), shorter spicules (135–145 vs 202–210 µm) and fewer male copulatory supplements (9 vs 14–16).From both species the new species differs by having a rounded tail vs convex-conoid or slightly subdigitate. Beside the newspecies, a population of Paraxonchium laetificans (Andrássy, 1956) Altherr & Loof, 1969 with relatively numerous males wasfound from forests of northern Iran. The male of this species, which had not been found in Iran so far and had been described on two specimens only, is described and illustrated in detail.